Bioethical aspects of robotics in surgery - Vvedenskaya, Elena (Array, 2021)
The article discusses the bioethical aspects of robotics in surgery and assesses the impact of this process on the relationship between the physician and the patient. An engineering model is gradually replacing the traditional paternalistic model of the physician-patient relationship. If paternalism implies the doctor"s attitude to the patient as his sick child, which requires compassion, help, and great responsibility on the part of the doctor, then when implementing the second model, the doctor, like a technical executor, performs only the responsibilities provided by the job description. On the one hand, the dominance of a technical-type model carries the threat of depersonalizing the patient and eliminating contact between the physician and the patient. On the other hand, this contributes to a radical change in the concept of medicine. Why people usually go to doctors? For establishing a diagnosis, prescribing a course of treatment, a prescription, and performing medical manipulations? Machines, leaving a human with a completely different role in the relationship between the physician and the patient, will increasingly perform these actions. The release of doctors from routine tasks will allow them to pay more attention to patient care, fully demonstrating their human qualities. The article analyzes the surgeon"s place in modern medicine and makes an attempt to determine which category the surgery belongs to, "machine territory" or "human territory".